Crafting cultural narratives: developing storybooks enriched with Bali’s local heritage to improve students' understanding of spiritual and social attitude - Mahartini, Komang Trisna; Suastra, I Wayan; Sudiana, I Nyoman; Gading, I Ketut; Sanjaya, Dewa Bagus (Edelweiss Applied Science and Technology, 2024)
Character education is the main focus of the learning process at the elementary school level in Indonesia. To support the implementation of character education, researchers developed children's stories enriched with local Balinese cultural values that teach spiritual understanding and social interaction. This study specifically aims to identify the effectiveness of the developed stories in building students' spiritual and social attitudes. This study was conducted using a single-shot case study design. Researchers involved one class of elementary school students in Bali. They were given a pre-test to measure spiritual and social attitude understanding before they were taught using the developed stories. After that, they were given a post-test to measure spiritual and social attitude understanding after they were taught using the developed stories. The pre-test and post-test data were analyzed quantitatively using paired-sample t-test inferential statistical analysis. The paired-sample t-test analysis showed that the difference in the pre-test and post-test results was significant. Thus, it can be concluded that implementing children's stories enriched with local Balinese cultural values has proven effective in shaping students' spiritual and social attitudes.